Proceedings of the 2011 SIAM International Conference on Data Mining - Liu, Bing 1963-; Liu, Huan 1958-; Clifton, Christopher W.; Washio, Takashi 1960-; Kamath, Chandrika (Society for Industrial and Applied Mathematics, SIAM, 2011)
Welcome to SDM 2011 -- The Eleventh SIAM International Conference on Data Mining, held in Mesa, Arizona. SDM 2011 continues the series of conferences focusing on the theory and practice of data mining as applied to data sets in science, engineering, biomedicine, and the social sciences, among others. The conference has a rich program; in addition to strong technical papers, there is also a broad set of tutorials, workshops and mini-symposia. Building on the success of the doctoral forum held in previous years, this year will see a continuation of this popular event. The strong program is also complemented by four keynote talks by renowned researchers from academia and industry: Chid Apte from IBM's T.J. Watson Research Center, Susan Dumais from Microsoft Research, Jiawei Han from University of Illinois at Urbana-Champaign, and Robert A. Stine, from University of Pennsylvania, who will share with us their experiences and visions
Keywords: Data mining; Congresses; Discrete mathematics and graph theory; Konferenzschrift